The time to passage of biological and complex motion - Mouta, Sandra (2012)
A significant part of human interactions occur with other human beings and not only with inanimate objects. It is important in everyday tasks to estimate the time it takes other people to reach (time to contact) or pass us (time to passage). Surprisingly, little is known about judging time to contact or time to passage of biological or other complex motions. In two experiments, rigid and non-rigid (biological, inverted, scrambled, and complex non-biological) motion conditions were compared in a time-to-passage judgment task. Subjects could judge time to passage of point-light-walker displays. However, due to relative and opponent movements of body parts, all articulated patterns conveyed a noisier looming pattern. Non-rigid stimuli were judged as passing sooner than rigid stimuli but reflected more uncertainty in the judgments as revealed by precision judgments and required longer reaction times. Our findings suggested that perceptual judgments for complex motion, including biological patterns, are built on top of the same processing channels that are involved on rigid motion perception. The complexity of the motion pattern (rigid vs. non-rigid) plays a more determinant role than the “biologicity” of the stimulus (biological vs. non-biological), at least concerning time-to-passage judgments.